Integration Remote Sensing and GIS Techniques to Evaluate Land Use-Land Cover of Baghdad Region and Nearby Areas - Ahmed, Mousa; Ahmad, Walid (Iraqi Journal of Science, 2023)
The study area of Baghdad region and nearby areas lies within the central part of the Mesopotamia plain. It covers about 5700 Km2. The remote sensing techniques are used in order to produce possible Land Use – Land Cover (LULC) map for Baghdad region and nearby areas depending on Landsat TM satellite image 2007. The classification procedure which was developed by USGS used and followed with field checking in 2010. Land Use-land cover digital map is created depending on maximum likelihood classifications (ML) of TM image using ERDAS 9.2.The LULC raster image is converted to vector structure, using Arc GIS 9.3 Program in order to create a digital LULC map. This study showed it is possible to produce a digital map of LULC and it can be constantly updated .The image was classified into five main classes, these are: Urban and Built-up land class, vegetated land class, Water class, Barren land class and Agricultural none vegetated land class. The accuracy assessment for classification was 93.70% and Kappa coefficient was 0.8833.